Deliberation, context, emotion and trust - understanding the dynamics of adults’ COVID-19 vaccination decisions in Germany - Dasch, Selina; Wachinger, Jonas; Bärnighausen, Till; Chen, Simiao; McMahon-Rössle, Shannon A. (BMC public health, 2023)
Background: Willingness to vaccinate against coronavirus disease 2019 (COVID-19), which is vital to successful vaccination campaigns, is wavering and suboptimal. In Germany, quantitative research highlighted concerns regarding the safety and efficacy of COVID-19 vaccines as barriers to uptake, but qualitative insights regarding individuals’ decisions about COVID-19 vaccines and how personal perceptions reflect or refute existing behavioral theories are lacking. Methods: To identify how individuals make COVID-19 vaccination decisions within real-life contexts, we conducted 33 semi-structured, in-depth qualitative interviews with individuals in Germany between March and April 2021 using maximum variation sampling, focusing on perceptions of COVID-19 vaccines. Analysis, informed by a framework approach, began in the field via debriefings and was amplified upon the conclusion of data collection. Results: Four interconnected themes (deliberation, context, emotion, trust) shaped respondents’ decisions about vaccination. Personal deliberation regarding benefits and risks of vaccines and perceptions of the broader social and political context sparked a spectrum of emotions that underpinned vaccination decisions. Trust in science and researchers emerged as a powerful protective factor facilitating the decision to get vaccinated even amidst a rapidly changing context and disconcerting information. Conclusions: Our findings add to ongoing debates about the breadth of vaccination decisions by highlighting how respondents are influenced by their perceptions of the political context and the emotional heft of their decisions. The role of cognitive evaluation, context, and emotions mirrors other decision-making frameworks, particularly the Risk as Feelings Theory. We extend on the elements of this theory by highlighting trust as a protective factor when making decisions particularly in highly uncertain contexts. Success of vaccination campaigns, more important than ever as new variants of COVID-19 emerge, is interwoven with an ability to bolster trust in science. Communicating public-health decisions and information about vaccines transparently without instilling fear offers promising chances to strengthen public trust in COVID-19 vaccines. Trial registration: German Clinical Trials Register (DRKS00024505).